Gauging Sarawak Identity through Connection with Indigenous Music (SICIM) - Collin, Jerome; Ting, Su Hie (Faculty of Education, Language and Communication, 2023)
Sarawakian identity consists of a myriad of knowledge, attitudes and behaviours that bring forth the soul of the land of the hornbill. Hidden among the multi-faceted dimensions of the Sarawakian identity is knowledge of Sarawak indigenous music which embodies the struggles and aspirations of Sarawakians in the past to the present. The project aims to determine the level of Sarawakian identity through knowledge and affiliation with Sarawak indigenous pop music. The Sarawakian identity gauge is based on the Iban Songs and Identity Questionnaire (IBSIQ) which has been copyrighted. However, here it is developed into the form of a fun quiz that expands beyond Iban pop songs to other Sarawak indigenous groups. The fun quiz is a product that will interest stakeholders in the tourism industry, the music industry as well as researchers in cultural heritage and arts. Its strength is that it is firmly anchored in empirical research but its arms extend to the public sphere and is capable of attracting the interest of the ordinary person on the streets. This project is under the PRamlee Grant (Music that Represents and Binds Us: Sarawak Indigenous Popular Music, Identity and Sense of Belonging), F09/PRC/2179/2021.